Nitrogen cycle in the Late Archean ferruginous ocean - Busigny, V.; Lebeau, O.; Ader, M.; Krapez, Bryan; Bekker, A. (Elsevier Science BV, 2013)
The Hamersley Group comprises a Late Archean sedimentary succession, which is thought to record the prelude to the atmospheric oxygenation in the Paleoproterozoic, the so-called Great Oxidation Event (GOE), at ~2.4 Ga. We studied drill-core samples of sedimentary rocks from the upper Mount McRae Shale and Brockman Iron Formation deposited before the GOE at ~2.5 Ga in order to characterize the environments and ecosystems prevailing during their deposition. The rocks from the Mount McRae Shale and Brockman Iron Formation represent, respectively, proximal euxinic conditions and distal ferruginous depositional environments, thus providing an opportunity to examine lateral variability in the open-marine basin. We analyzed the concentration and isotopic composition of carbon in carbonate and organic matter, bulk nitrogen content and its isotopic composition as well as major element concentrations. The δ13Ccarb values and carbonate content range from -3.2 to -10.7‰ and 0.1 to 58 wt.%, respectively. Organic carbon content also varies over a large range from 0.05 to 4.6 wt.% with a near constant δ13Corg value of-28.7 ± 0.8‰. Negative δ13Corg excursions (down to -31‰) are generally correlated with high organic matter content. Bulk nitrogen shows highly variable concentration, between 1.3 and 785 ppm, and δ15N values between 0.4 and 13.4‰.The δ13Ccarb values reflect a diagenetic carbonate origin, with negative values typical for Fe-rich carbonates formed by organic matter mineralization with ferric oxyhydroxides. In contrast, δ13Corg and δ15N values record primary isotope signatures derived from ancient living organisms. The relatively constant δ13Corg values at around -28.7‰ are interpreted as reflecting photoautotrophs utilizing a large pool of dissolved inorganic carbon. Inverse stratigraphic co-variation between δ15N and δ13Ccarb values was observed for the Brockman Iron Formation. We propose that N and C biogeochemical cycles were coupled by Fe redox cycling in the water column and in sediments of the Late Archean ocean. Several models for biogeochemical N cycling linked to the redox structure of the water column are considered. Under fully anoxic conditions, the dominant N species available for assimilation by micro-organisms in the photic zone could be ammonium (NH4 +). Highly positive δ15N values would reflect the assimilation of NH4 + enriched in 15N by partial oxidation to nitrite, followed by quantitative removal of the produced nitrite by denitrification or anamox processes.Ammonium oxidation could have been driven by (i) O2 produced locally via oxygenic photosynthesis, or (ii) microbial oxidation utilizing Fe(III)-oxyhydroxides formed in the water column. Under redox-stratified conditions, N assimilated by primary producers could have been in the form of NO3 -, based on modern and Phanerozoic analogs. The positive δ15N values would have resulted in this case from partial denitrification of NO3 - coupled to anaerobic microbial oxidation of Fe(II) to Fe(III). We conclude that similar positive δ15N signatures may record very different N biogeochemical cycles under anoxic, stratified and fully oxic conditions in the ocean. Interpretation of the N isotopes in terms of N biogeochemical cycle thus requires independent constraints on the redox structure of the ocean.